Real and Financial Tradeoffs in Non-Listed Firms: Cash Flow Sensitivities and How They Change with Shocks to Firms' Main-Bank - Charlotte Ostergaard; Amir Sasson; Bent E. Sørensen (Norges Bank, 2010)
We study how non-listed firms trade off financial, real, and distributive uses of cash. We show that firms' marginal value of cash (MVC) affects the mix of external and internal finance used to absorb fluctuations in cash flows; in particular, high-MVC firms employ substantially more external finance on the margin. Linking firms to their main bank, we find that shocks to bank finance affect corporate trade-offs and have real effects in high-MVC firms, making investment more sensitive to firm cash flows. Our analysis suggests that external finance constraints affect the real economy via firms' marginal value of cash.
hdl:11250/2497434
Keywords: 330; cash management; cash holdings; cost of external finance; non-listed firms; bank lending channel